Clinical effectiveness of magnesium orotate in patients with cardiac arrhythmias, arterial hypertension, and mitral valve prolapse - E. V. Akatova; O. P. Nikolin; A. I. Martynov (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the effectiveness of magnesium orotate in the patients with cardiac arrhythmias, arterial  hypertension (AH), and idiopathic mitral valve prolapse (MVP). Material and methods. The complex examination, dynamic follow-up, and placebo-controlled differentiated  treatment were performed in 84 patients with idiopathic MVP. All participants underwent echocardiography,  24-hour blood pressure monitoring (BPM) and electrocardiography (ECG) monitoring, office BP measurement,  spectral analysis of heart rate variability (HRV), and physical stress test. The main group (MG; n=43) received  magnesium orotate (3000 mg/d) for 6 months; the comparison group (CG; n=41) received placebo. Results. According to the 24-hour ECG monitoring data, the treatment was associated with disappearance of  high-grade arrhythmias and a 40% reduction in supraventricular (paroxysmal and non-paroxysmal) tachycardia  incidence. The number of ventricular extrasystoles was reduced in 26%, and they disappeared in 54%. In 8%,  polytopic ventricular extrasystoles were substituted by occasional monotopic extrasystoles. These changes were not  observed in the CG patients. The percentage of Stage I AH patients decreased from 38% to 8% in the MG, and  from 30% to 20% in the CG. Conclusion. In MVP patients, magnesium orotate treatment improved electro-physiological heart parameters,  with reduced supraventricular and ventricular extrasystole incidence and improved circadian BP profile.